The Implementation of the Good Faith Principle in Unbalanced Banking Credit Agreements Based on Substantive Justice - Sryani Br. Ginting; Christina N.M. Tobing (Universitas Pelita Harapan, 2026)
Contracts as legal instruments, play a vital role in business activities, which can be viewed not only from a normative aspect but also through philosophical and economic dimensions. Ideally, the formation of contractual relationships is based on fundamental principles to ensure the realization of fairness and equity for all parties involved. One of the primary principles determining the quality of justice in a contract is good faith, which serves as a guideline for the interpretation and execution of agreements. This research aims to analyze the regulation of good faith in national contract law, examine its application in bank credit agreements which often exhibit an imbalance in the parties' positions and formulate a regulatory model oriented toward substantive justice. The research method employed is normative legal research. The approaches used include statutory, conceptual, and case-based approaches. The results indicate that the principle of good faith in Indonesian contract law (the Civil Code) possesses both juridical and philosophical meanings aligned with John Rawls’ theory of justice and the values of Pancasila. Good faith must be interpreted by judges in their rulings in concreto and systematically to ensure clarity of meaning through